PERAN BIDAN DALAM MENGHADAPI KEKERASAN TERHADAP PEREMPUAN: LITERATURE REVIEW - Nasution, Ria Niari; Nasution, Nadhiati Awlia; Terawan, Vita Murniati; Sari, Puspa; Arisanti, Nita; Susiarno, Hadi; Nurihsan, Juntika (Media Penelitian dan Pengembangan Kesehatan, 2024)
Violence against women is a complex health problem that can affect their lives and even those around them. Cases of violence against women have an impact on physical, psychological/mental, reproductive, and economic health and even have an effect on the health of children who are cared for by the mothers of victims of violence. The prevalence of violence against women in Indonesia in the Simfoni PPA data reported and recorded during 2020-2023 increased by 2,774 cases. Violence against women requires the active role of professional health workers, especially midwives, in conducting screening, approach and support, following up on collaborations/referrals, In addition, midwives must also develop themselves through special learning or training so that they are able to provide education to increase awareness. This study aimed to explore the management of midwifery implementation regarding violence against women. The method used in this literature review study is based on the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) checklist. Searches were conducted from PubMed, Science Direct, and Sage Journals to identify articles published between January 1, 2020, and May 1, 2024 with the keywords “violence against women, intimate partner violence, midwifery care of violence, health care of violence”. The results of the review from 703 journals obtained 9 relevant journals regarding the management of midwifery implementation including early detection through routine screening, training and education for midwives, collaboration/referral with various other sectors, empowering women, documentation, and evaluation.